A Salivary α-Amylase Level in Relation to the Oral Health Parameters among Children in Baghdad City - Ameena R Diajil; Lamia I Sood; Rasha A Azeez (College of Dentistry/ University of Baghdad, 2016)
Background: Saliva is a specific bio-fluid with important biomarkers. Analyzing any alternation in these markers could give valuable information, in relation to oral health status parameters. The aim of this study was to investigate the level of α -amylase in unstimulated whole saliva of healthy, primary school children in relation to some oral health parameters. Materials and Methods: A questionnaires consisted of demography and medical histories of participants were filled by children families. Saliva samples were collected for 5- minutes between 9:00 -11:00 AM from 114 healthy students aged 6-13 years, divided into four age groups. Flow- rate, Plaque and Gingival Index were assessed and dentition status was investigated by DMFT/dmft using WHO criteria. Salivary amylase was analyzed in unite per litter, using quantitative colorimetric amylase determination at 585nm. Results: A significant positive correlation was found between age and salivary flow-rate, (r=0.362, P < 0.001). Salivary α-amylase concentration increased significantly with age (P< 0.001). For each one year there is an increase in age, amylase level is expected to increase by 5.2 U/L. A male gender is expected to reduce salivary α -amylase level by 10.6 U/L compared to female, however the effect was not significant. Gingival index was positively, although non-significantly associated with salivary α -amylase concentration. DMFT showed a significant weak positive linear correlation with salivary amylase level (r=0.309, P